Critical heat flux measurement and visualization in R-134a on a vertical single rod with and without mixing-vanes spacer: The characteristics and phenomenon of critical heat flux. (15th September 2021) - Liu, Yang; Liu, Wei; Shan, Jianqiang; Novog, David R.; Zhang, Bo; Gui, Miao; Guo, Junliang
Highlights: A visualized CHF experiment was carried out under the similar range and geometry with PWRs. The CHF database, experimental trends and comparisons to existing CHF prediction methods were presented. Three boiling phenomena are observed at CHF, and the possible CHF mechanism was explained. Quantitative analysis of bubble layer thickness was carried with/without mixing-vanes spacer. Abstract: In this study, a critical heat flux (CHF) experiment using R-134a as working fluid was carried out in a vertical single rod geometry. A unique feature of this experiment are high speed visualization studies obtained at a viewing port located at the CHF location. The 9.5 mm O.D. heated rod was placed in a 19 x19mm square channel to simulate the Pressurized Water Reactors (PWRs) fuel lattice. Test conditions were selected and scaled to cover a wide range of water conditions relevant to PWRs. The CHF database, experimental trends and comparisons to existing CHF prediction methods are presented. The visualization results of the flow boiling at the CHF location and the CHF mechanism are discussed with a particular emphasis on the impact of grid spacers on the boiling phenomena. Quantitative analysis of bubble layer thickness is carried out, including the relationship between bubble layer thickness and CHF.